La lettre de suicide du Premier Ministre ‘Abd al-Muḥsin al-Sa‘dūn - Aline Schlaepfer (Revue des Mondes Musulmans et de la Méditerranée)
More than a decade after the withdrawal of Ottoman administration from the Empire’s Iraqi provinces, in November 1929, Iraqi Prime Minister, ‘Abd al-Muḥsin al-Sa‘dūn committed suicide by shooting himself to the heart leaving a note in Ottoman Turkish to his son ‘Alī. This article explores the dynamics for a “Hashemite memory of state” under the monarchy of Fayṣal, centered on a supposedly homogenous and immemorial Arabness. In particular, I ask whether there could have existed, in the shadow of official memory, a multiplicity of marginal memories. A close reading of the Prime Minister’s political and personal trajectory – between his Ottoman Turkish socio-political background and the mounting tensions with Southern Iraqi Shi‘ite leadership – exposes complex issues of identity politics behind claims of Arabness. The legacy of the Turkish language: amnesia or indifference?